Genomic analysis and antimicrobial activity of β-lactam/β-lactamase inhibitors and other agents against KPC-producing Klebsiella pneumoniae clinical isolates from Brazilian hospitals - Camargo, Carlos Henrique; Yamada, Amanda Yaeko; de Souza, Andreia Rodrigues; Cunha, Marcos Paulo Vieira; Ferraro, Pedro Smith Pereira; Sacchi, Claudio Tavares; dos Santos, Marlon Benedito; Campos, Karoline Rodrigues; Tiba-Casas, Monique Ribeiro; Freire, Maristela Pinheiro; Barretti, Pasqual [UNESP] (Springer Nature, 2023)
Carbapenem-resistant Klebsiella pneumoniae (CRKP) are highly disseminated worldwide, and isolates co-resistant to other antimicrobial agents pose a threat to effective antimicrobial therapy. Therefore, evaluation of novel antimicrobial drugs is needed to identify potential treatments with better outcomes. We evaluated the in vitro activity of novel antimicrobial drugs/combinations against 97 KPC-producing Klebsiella pneumoniae isolates recovered from different hospitals in Brazil during 2021–2022. Clonality, resistance and virulence genes were detected by whole-genome sequencing. The majority of the isolates (54.6%) were classified as extensively drug resistant or multidrug resistant (44.3%); one isolate showed a pandrug resistance phenotype. The most active antimicrobial agents were meropenem-vaborbactam, cefiderocol, and ceftazidime-avibactam, with sensitivities higher than 90%; resistance to ceftazidime-avibactam was associated with KPC-33 or KPC-44 variants. Colistin and polymyxin B were active against 58.6% of the isolates. The 97 isolates were distributed into 17 different sequence types, with a predominance of ST11 (37.4%). Although high in vitro susceptibility rates were detected for meropenem-vaborbactam and cefiderocol, only ceftazidime-avibactam is currently available in Brazil. Our findings showed limited susceptibility to antimicrobial drugs employed for infection treatment of carbapenem-resistant K. pneumoniae, underscoring the urgent need for stringent policies for antimicrobial stewardship to preserve the activity of such drugs.